Robust command governors for constrained linear systems - Casavola,A; Mosca,E; Angeli,D (IEEE Transactions on Automatic Control, 2000)
Robust command governors are designed for discrete-time linear time-variant (LTV) system with polytopic uncertainty models and subject to unknown bounded disturbances and pointwise-in-time input and state-related constraints.